2002
DOI: 10.1128/jb.184.16.4536-4543.2002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Coexpression ofBorrelia burgdorferiErp Proteins Occurs through a Specific,erpLocus-Directed Regulatory Mechanism

Abstract: An individual Borrelia burgdorferi bacterium can encode as many as 13 different Erp (OspE/F-related) proteins from mono-and bicistronic loci that are carried on up to 10 separate plasmids. We demonstrate through multilabel immunofluorescence analyses that individual bacteria simultaneously coexpress their entire Erp protein repertoire. While it has been proposed that B. burgdorferi controls expression of Erp and other plasmid-encoded proteins through changes in DNA topology, we observed regulated Erp expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…The nucP gene product likewise had not previously been functionally characterized. An earlier study by our laboratory gave this gene the placeholder name bppA (Borrelia plasmid protein A) (23). Subsequent Blast-P analyses of the predicted gene product found modest similarities with some bacteriophage-encoded nucleases (e.g., an E value of 10 5 similarity to LHK-Exo exonuclease of Laribacter hongkongensis) (62).…”
Section: Resultsmentioning
confidence: 99%
“…The nucP gene product likewise had not previously been functionally characterized. An earlier study by our laboratory gave this gene the placeholder name bppA (Borrelia plasmid protein A) (23). Subsequent Blast-P analyses of the predicted gene product found modest similarities with some bacteriophage-encoded nucleases (e.g., an E value of 10 5 similarity to LHK-Exo exonuclease of Laribacter hongkongensis) (62).…”
Section: Resultsmentioning
confidence: 99%
“…Erp proteins are major candidates for surface proteins interacting with the immune system of the host. Along these lines, it was demonstrated that erp genes are transcribed during all stages at which spirochetes encounter host's serum [30] and multiple different Erp proteins are simultaneously expressed on the bacterial surface [31,32]. Thus, the ability to bind complementinhibiting factors, such as factor H and FHL-1, seems critical for immune evasion of the pathogen in a wide variety of hosts and this activity appears to be dependent on specific recognition motifs of individual Erp proteins.…”
Section: Discussionmentioning
confidence: 99%
“…All the erp coding sequences, including erpA, erpC, and erpP, are preceded by almost identical 5′-non-coding sequences, including binding sites for at least 3 distinct DNA-binding proteins (Babb et al, 2004. Co-regulation of erp genes on different cp32 plasmids suggests the existence of similar molecular mechanisms that could coordinate expression of genes encoding BbCRASP-3, -4, and -5 at the transcriptional level Babb et al, 2001;El-Hage and Stevenson, 2002;Babb et al, 2004Babb et al, , 2006.…”
Section: Molecular Mechanisms Underlying Expression Of Bbcraspsmentioning
confidence: 99%